Faktor-Faktor yang Mempengaruhi Kebijakan Dividen pada Sektor Energi Periode 2022-2024 - Sastrawan, I Komang Yuda; Dewi, Gst. Ayu Ketut Rencana; Atmaja, I Made Dwita (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of profitability, firm size, investment opportunity set (IOS), and institutional ownership on dividend policy in energy sector companies listed on the Indonesia Stock Exchange. Dividend policy is an important financial decision because it reflects company performance and serves as a consideration for investors in making investment decisions. This research employs a quantitative approach with an associative method using secondary data in the form of financial statements of energy sector companies during the research period. The sample was selected using purposive sampling. Data analysis was conducted using multiple linear regression preceded by descriptive statistical tests, classical assumption tests, and hypothesis testing. The results show that profitability and IOS have a positive and significant effect on dividend policy. This indicates that companies with higher profitability and better investment opportunities tend to have a greater ability to distribute dividends and provide positive signals regarding future performance prospects. In contrast, firm size has a negative and insignificant effect, while institutional ownership has a positive but insignificant effect. These findings suggest that company scale and institutional ownership are not necessarily the main determinants of dividend policy in energy sector companies.